HIGH EFFICIENCY SHOOT AND ROOT FORMATION FROM COTYLEDONARY NODES OF COTTON (GOSSYPIUM HIRSUTUM L.) - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2008)
The Purpose of this Study was to develop an efficient micropropagation system for cotton (Gossypium hirsutum L.), a worldwide commercially important fiber crops. In this study, successful shoot and root induction were achieved from cotyledonary nodes of two different cotton genotypes, Nazilli 84S and Cukurova 1518 which are widely planting in Turkey. Plant tissue culture systems were established on Murashige and Skoog (MS) media supplemented with various plant growth regulators using cotyledonary nodes with hypocotyl pieces as explant. Explants were placed on different MS media Supplemented with different combinations of kinctin (KIN) and alpha-Naplitaleneacetic acid (NAA). Seven-day-old explants were used and germination, regeneration and rooting processes were consisted in 5 weeks. The best regeneration responses were from cotyledonary nodes of Nazilli 84S - 80% and Cukurova 1518 - 75%. Successful direct regeneration and rooting were obtained and significant differences were not seen between two genotypes. In addition, regenerated young plants were phenotypically normal and they set seeds. This rapid in vitro regeneration and rooting procedure can be also available for use of particle gun and Agrobacterium-mediated transformation.
Keywords: PLANT-REGENERATION; SOMATIC EMBRYOGENESIS; SUSPENSION-CULTURES; TRANSFORMATION; EXPLANTS; TISSUE